The Influence of Using Microsoft PowerPoint Learning Media on Learning Outcomes in Business Law Courses - Muhammad Fazrin; Muhammad Rahmatullah; Mahmudah Hasanah; Monry Fraick Nicky Gillian Ratumbuysang (Politeknik Pertanian Negeri Samarinda, 2024)
This study aims to determine the effect of using Microsoft PowerPoint learning media on the learning outcomes of FKIP ULM Economics Education students class of 2018 and 2019 in the Business Law course. This type of research is quantitative research with the Quasi Exsperimental Design method. This study used a Non Equivalent Control Group Design. The research sample as a control class is the 2018 class of Economic Education students totaling 23 people and the 2019 class of Economic Education students as an experimental class totaling 28 people. The sampling technique was purposive sampling. The instruments used in this study were questions on the pretest and posttest. The data analysis techniques used in this study were normality test, homogeneity test, N-Gain test and T test using SPSS V. 16 for Windows. 16 for Windows. Based on the results of the T-test calculation, the sig. (2 tailed) of 0.280. Because 0.280 > 0.05 then H0 is rejected. This shows that there is no significant difference in the learning outcomes of Business Law courses between the control group (classes without using interactive learning media Microsoft PowerPoint ) and the experimental class (classes that use interactive learning media Microsoft PowerPoint). It can be concluded that the use of Microsoft PowerPoint learning media on the learning outcomes of FKIP ULM Economics Education students class of 2018 and 2019 has no significant effect on Business Law courses.